Utilization of ICT for teaching and learning in Malaysian institutions of higher education - Reh, Hafizah; Raja Mohd., Noorhazwani; Muhd. Adnan, Nurul Izwah; Shahwan, Siti Eisyah; Zeki, Ahmed M. (2009)
With the rapid development of ICT, the traditional approach of teaching and learning at higher education institutions is also changing. In fact, the integration between education and ICT can contribute towards a knowledge-base society. The past two decades have witnessed an emerging and growing trend towards the implementation of ICT in universities to support the process of teaching and learning. This paper aims at studying the issues of integrating ICT tools in education which can lead to the success of such implementation. Two aspects are identified, one is more toward the policies such as educational policies, teaching and learning assessment, professional development, and financial aspects. While the second one includes restructuring the curricula, creating activities for students, creating students-centered learning environment, and establishing links between societies, parents and higher education. The paper also attempts to discuss the adoption of e-learning as an educational tool for teaching and learning in the universities in Malaysia.